Development of university level education in the Łódź Voivodeship - Wolaniuk, Anita (Acta Geographica Lodziensia, 2019)
The author has presented a historical outline of the development of university level education in the Łódź Voivode-ship, especially during periods of centrally planned economy (1945–1989) and free market economy (since 1990). Numbers of higher education institutions (public and non-public), of students, of graduates and of academic teachers were analysed. Church and military schools were not considered, because data concerning them were not provided, neither by the Statistics Poland nor by the Łódź Voivodeship Statistical Office. The distribution of extraneous university branches (operating outside Łódź City and even outside of the Łódź Voivodeship) was also discussed.